An Antimicrobial Evaluation of Bhasmeshwara Rasa on Salmonella Typhi (International Journal of Ayurveda and Pharma Research, 2024)
Infections can be caused by a wide range of pathogens and bacteria are one among them. Presently, we confront a significant challenge concerning antimicrobial resistance, leading the world to explore alternative medicine as a potential solution. Bhasmeshwara rasa is a formulation mentioned under Sannipataja jwara chikitsa in Rasendra Chintamani which acts on all three Doshas. It is a Khalviya Rasayana containing Vanyopala bhasma (cow dung cake Bhasma), Maricha and Shuddha vatsanabha and its Anupana is Ardraka Swarasa.Even though there is no Parada used in this formulation, still this formulation is suffixed with “Rasa” in its name Bhasmeshwara. In vitro anti-bacterial study, the action of Bhasmeshwara rasa was tested against Salmonella typhi by well diffusion method. A combination of Bhasmeshwara Rasa and Ardraka Swarasa showed antibacterial activity against Salmonella typhi. Hence, with the present study, it can be concluded that Bhasmeshwara Rasa and Ardraka Swarasa combination shows mild to moderate anti-bacterial activity.